Forensic accounting in fraud detection and prevention: A qualitative investigation of microfinance institutions - Grace Osariemen Eghe-Ikhurhe; Naheed Nawazesh Roni; Mandella Osei Assibey Bonsu (International Journal of Management, Economics and Social Sciences (IJMESS), 2024)
Despite authorities and governments' efforts in fraud prevention and investigation, new types of fraud emerge daily. In fact, the rise in global business scandals has heightened the need for forensic accounting, as financial fraud is the world's most severe economic threat. Forensic accounting combines accounting, auditing, and investigative skills to detect and prevent accounting fraud. Research on fraud investigations and forensic accounting has predominantly employed quantitative methods, with relatively few studies utilizing qualitative research approaches. Therefore, this study fills the gap and examined the role of forensic accounting in fraud detection and prevention of microfinance in Nigeria. A qualitative approach was employed using a sample of eighteen participants working in Nigerian microfinance firms. The results show that advanced technological skills in forensic accounting can enhance the integrity of microfinancing institutions in Nigeria, preventing fraud and gain investor and shareholder confidence. In addition, the results reveal that, the future of microfinance forensic accounting is expected to prioritize technological advancements like data analytics, machine learning, artificial intelligence, and blockchain in its procedures. By implication, forensic accounting is crucial for Nigerian microfinance institutions; management must recognize its importance in implementing proactive measures to prevent fraud.
Keywords: M41; M42; N27; 330; Forensic accounting; microfinance institutions; fraud; technology; Nigeria